Potential of polymethacrylate pseudo crown ethers as solid state polymer electrolytes. Issue 51 (13th June 2017) - Moins, S.; Martins, J. C.; Krumpmann, A.; Lemaur, V.; Cornil, J.; Delbosc, N.; Decroly, A.; Dubois, Ph.; Lazzaroni, R.; Gohy, J.-F.; Coulembier, O.
Abstract : The association of kinetic studies, DFT calculations and 1 H– 7 Li NMR analyses allowed the control of the cyclo -ATRP of PEG9 DMA and the production of polymethacrylate pseudo crown-ethers of various molar masses. Abstract : The association of kinetic studies, DFT calculations and 1 H– 7 Li NMR analyses allowed the control of the cyclo -ATRP of PEG9 DMA and the production of polymethacrylate pseudo crown-ethers of various molar masses. Their potential to act as a solid-state polymer electrolyte in Li-ion batteries has been highlighted and may come from the supramolecular organization of the cyclo -PEG forming a Li + diffusion channel.